The Marine Mammal Class II Major Histocompatibility Complex Organization - Sá, André Luiz Alves de; Breaux, Breanna; Burlamaqui, Tibério Cesar Tortola; Deiss, Thaddeus Charles; Sena, Leonardo; Criscitiello, Michael Frederick; Schneider, Maria Paula Cruz (Frontiers in Immunology, 2019)
Sirenians share with cetaceans and pinnipeds several convergent traits selected for the aquatic lifestyle. Living in water poses new challenges not only for locomotion and feeding but also for combating new pathogens, which may render the immune system one of the best tools aquatic mammals have for dealing with aquatic microbial threats. So far, only cetaceans have had their class II Major Histocompatibility Complex (MHC) organization characterized, despite the importance of MHC genes for adaptive immune responses. This study aims to characterize the organization of the marine mammal class II MHC using publicly available genomes. We located class II sequences in the genomes of one sirenian, four pinnipeds and eight cetaceans using NCBI-BLAST and reannotated the sequences using local BLAST search with exon and intron libraries. Scaffolds containing class II sequences were compared using dotplot analysis and introns were used for phylogenetic analysis. The manatee class II region shares overall synteny with other mammals, however most DR loci were translocated from the canonical location, past the extended class II region. Detailed analysis of the genomes of closely related taxa revealed that this presumed translocation is shared with all other living afrotherians. Other presumptive chromosome rearrangements in Afrotheria are the deletion of DQ loci in Afrosoricida and deletion of DP in E. telfairi. Pinnipeds share the main features of dog MHC: lack of a functional pair of DPA/DPB genes and inverted DRB locus between DQ and DO subregions. All cetaceans share the Cetartiodactyla inversion separating class II genes into two subregions: class IIa, with DR and DQ genes, and class IIb, with non-classic genes and a DRB pseudogene. These results point to three distinct and unheralded class II MHC structures in marine mammals: one canonical organization but lacking DP genes in Pinnipeds; one bearing an inversion separating IIa and IIb subregions lacking DP genes found in cetaceans; and one with a translocation separating the most diverse class II gene from the MHC found in afrotherians and presumptive functional DR, DQ and DP genes. Future functional research will reveal how these aquatic mammals cope with pathogen pressures with these divergent MHC organizations.